The effect of emotional labour on work satisfaction and emotional display behaviour - Rury Siti Ruhaniah; Rayini Dahesihsari (Universitas Ahmad Dahlan, 2019)
Improving the quality of service in the hospitality industry is a strategic agenda that enables the increase of foreign exchange income. Internal factors affect the quality of service, particularly factors related to emotional processing (emotional labour) of service workers that are associated with the display of an expected emotional expression (emotional display behaviour) when providing services. Furthermore, another essential aspect to consider how to express the expected emotional expression well while also maintaining work comfort (job satisfaction) of the service providers. This research explored the effect of emotional labour on emotional display behaviour and job satisfaction. The study was conducted in a 5-star hotel, involving 94 front liner employees selected through convenience sampling. The study used the Surface and Deep Act Scale, Management Behavior Scale and MSQ-Short Scale. One-way ANOVA was used to analyze the data. The results showed that emotional labour profile had a positive effect on job satisfaction but not on emotional display behaviour. Therefore emotional labour as a personal capital needs to be addressed to enhance job satisfaction.